Epinephrine Use during Newborn Resuscitation - Kapadia, Vishal S.; Wyckoff, Myra H. (Frontiers in Pediatrics, 2017)
Epinephrine use in the delivery room for resuscitation of the newborn is associated with significant morbidity and mortality. Evidence for optimal dose, timing, and route of administration of epinephrine during neonatal resuscitation comes largely from extrapolated adult or animal literature. In this review, we provide the current recommendations for use of epinephrine during neonatal resuscitation and also the evidence behind these recommendations. In addition, we review the current proposed mechanism of action of epinephrine during neonatal resuscitation, review its adverse effects, and identify gaps in knowledge requiring urgent research.